2005
DOI: 10.1177/1087057105280070
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional In Vitro Reaggregates of Embryonic Cardiomyocytes: A Potential Model System for Monitoring Effects of Bioactive Agents

Abstract: To understand the physiological effects of substances used in drugs and therapies on heart muscle tissue, model systems that mirror the in vivo situation of living tissues are required. Therefore, the creation of 3-dimensional (3D) cell aggregates provides an improved and refined in vitro model as a link between cell-free or single cells and organs or whole organisms in vivo. Here we have characterized a stable contracting in vitro tissue model, which consists of embryonic chicken cardiomyocytes. For establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…13 A suitable 3D substrate to support organizational cultures has been applied to liver cells, cardiac cells, and solid tumors to attain morphological structure and maintain the integrity of intercellular signaling mechanisms. 15,[28][29][30] Collagen, a major constituent of the ECM, 31 has consistently been shown to support the development of the embryoid bodies. The microfilaments supporting structural collagen likely enable the cells to grow and organize naturally into an in vivo-like morphology.…”
Section: Discussionmentioning
confidence: 99%
“…13 A suitable 3D substrate to support organizational cultures has been applied to liver cells, cardiac cells, and solid tumors to attain morphological structure and maintain the integrity of intercellular signaling mechanisms. 15,[28][29][30] Collagen, a major constituent of the ECM, 31 has consistently been shown to support the development of the embryoid bodies. The microfilaments supporting structural collagen likely enable the cells to grow and organize naturally into an in vivo-like morphology.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 These processes have led to the formation of several different micro-tissue spheroids including bile canniculi 11 and beating cardiomyocytes. 12,13 LaMarca et al created 3D trophoblast aggregates of the SGHPL-4 cell line and demonstrated that the 3D configuration induced the invasive properties of these cells. This important study illustrated that trophoblast cells cultured in 3D have functional behavior strikingly different from those in monolayer.…”
Section: Discussionmentioning
confidence: 99%
“…Establishment of spheroids followed a modified protocol of Bartholomä et al [2005]. Fertile chicken eggs (white Leghorn) were incubated at 37 8C.…”
Section: Cell Culturementioning
confidence: 99%